A bimetallic fenton-like catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202610969226.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]目前,已有一些关于氮化硼基催化剂用于污染物降解的报道,但多数制备工艺复杂,或涉及贵金属,成本较高,且针对抗生素废水的高效降解仍面临挑战
1)制备方法简单、成本低廉:本发明采用廉价易得的硼酸、尿素和氟硼酸金属盐为原料,通过简单的溶液混合、油浴蒸干和两步热解工艺,即可制得目标催化剂,无需复杂设备和苛刻条件,易于规模化生产。
Smart Images

Figure CN122999248A_ABST
Abstract
Description
Technical Field
[0001] This application relates to a bimetallic Fenton catalyst, its preparation method, and its application, belonging to the field of catalyst technology. Background Technology
[0002] Antibiotic-like pollutants are frequently detected in aquatic environments, and traditional physical and biological treatment methods are insufficient to effectively remove these recalcitrant organic pollutants. The persulfate-based Fenton-like reaction is a typical advanced oxidation technique that generates highly oxidizing sulfate radicals (SO4·4·5H2O). - It has excellent degradation ability for organic pollutants such as antibiotics, and has attracted widespread attention from researchers.
[0003] Currently, there are some reports on the use of boron nitride-based catalysts for pollutant degradation, but most of them involve complex preparation processes or precious metals, resulting in high costs. Furthermore, achieving efficient degradation of antibiotic wastewater remains a challenge. For example, some catalysts are prone to metal ion leaching, causing secondary pollution; or the catalysts have low utilization rates for persulfate, leading to high reagent consumption. Therefore, developing a non-precious metal boron nitride-based catalyst with a simple preparation method, low cost, excellent catalytic activity, and high oxidant utilization rate for the efficient treatment of antibiotic-containing wastewater has significant practical application value. Summary of the Invention
[0004] In view of this, this application first provides a method for preparing a bimetallic Fenton catalyst. The preparation method is simple and low in cost, and can realize the preparation of non-precious metal boron nitride-based catalytic materials with excellent catalytic activity and high oxidant utilization.
[0005] Specifically, this application is implemented through the following scheme: A method for preparing a bimetallic Fenton catalyst, comprising the following steps: Step 1: Fluoroborate metal salt and boric acid are mixed in deionized water and ultrasonicated to obtain solution A, wherein the fluoroborate metal salt contains at least two metal salts; urea is dissolved in deionized water solution and ultrasonicated to obtain solution B. Step 2: Mix solution A and solution B, evaporate to dryness in an oil bath to obtain the precursor, place the precursor in a tube furnace, and perform initial pyrolysis under a nitrogen atmosphere. Step 3: Add fluorinating agent to the pyrolysis product, mix and place in a tube furnace for re-pyrolysis under nitrogen atmosphere to obtain bimetallic Fenton catalyst.
[0006] Boron nitride (BN), as a novel two-dimensional material, possesses excellent chemical stability, thermal stability, and high specific surface area. However, single boron nitride materials have limited catalytic active sites, often resulting in low catalytic efficiency. This application utilizes a one-step primary pyrolysis combined with a secondary fluorination / re-pyrolysis process to prepare a boron nitride-based catalytic material with a plate-like morphology, rich in bimetallic active centers, and a fluorine-modified surface, which can effectively improve the catalytic performance of boron nitride.
[0007] Furthermore, as a preferred option: In step one, The fluoroborate metal salt is any two of ferrous fluoroborate hexahydrate, copper fluoroborate hexahydrate, cobalt fluoroborate hexahydrate, lead fluoroborate, and indium fluoroborate.
[0008] The duration of the ultrasound is 10–30 min, the frequency is 20–40 kHz, and the input power is 100–200 W to ensure that the reactants are fully dissolved and dispersed.
[0009] The mass ratio between any two fluoroborate metal salts in the bimetallic precursor is 1:1 to 16:1. By adjusting the ratio of the two metal salts, the synergistic catalytic effect between the bimetals can be optimized. More preferably, the mass ratio of ferrous fluoroborate hexahydrate to any one of lead fluoroborate, copper fluoroborate hexahydrate, cobalt fluoroborate hexahydrate, and indium fluoroborate is 1:1 to 16:1 to form bimetallic precursors Fe / Pb, Fe / Cu, Fe / Co, and Fe / In; or the mass ratio of copper fluoroborate hexahydrate to any one of cobalt fluoroborate hexahydrate, lead fluoroborate, and indium fluoroborate is 1:1 to 16:1 to form bimetallic precursors Cu / Co, Cu / Pb, and Cu / In.
[0010] The molar ratio of urea to boric acid is 1:1 to 16:1, and preferably 1:1 to 6:1.
[0011] The ratio of the total mass of urea and boric acid to the mass of fluoroborate metal salt is 4:1 to 7:1.
[0012] In step two: The oil bath temperature for drying in the oil bath is 45–65 °C.
[0013] The oil bath evaporation time is 6–12 hours, until the deionized water is completely evaporated. This process is beneficial for urea, boric acid, and metal ions to form a uniform precursor complex.
[0014] The oil bath evaporation process is accompanied by stirring at a speed of 500–850 rpm.
[0015] The initial pyrolysis temperature is 800–1000 °C.
[0016] The duration of the initial pyrolysis is 1 to 3 hours.
[0017] The initial pyrolysis heating rate is 3–6 °C / min.
[0018] During the initial pyrolysis, urea, as a nitrogen source, reacts with boric acid to generate boron nitride. At the same time, the metal salt of fluoroborate decomposes, allowing metal atoms to be doped into the boron nitride lattice or loaded onto its surface.
[0019] In step three: The fluorinating agent is at least one of ammonium fluoride, ammonium hydrogen fluoride, sodium fluoride, and calcium fluoride. Ammonium fluoride and the like decompose during heating, and the released active fluorine species can react with the surface of boron nitride to achieve mild secondary fluorination.
[0020] The mass ratio of the fluorinating agent to the primary pyrolysis product is 1:1 to 1:3.
[0021] The mixing is performed by grinding. The product obtained from pyrolysis is added and ground evenly using a ball mill. More preferably, the grinding time is 2 to 4 hours and the grinding speed is 300 to 500 rpm.
[0022] The temperature for the re-pyrolysis is 350–550 °C.
[0023] The duration of the re-pyrolysis is 1 to 3 hours.
[0024] The heating rate for the re-pyrolysis is 2–4 °C / min.
[0025] The aforementioned re-pyrolysis achieves low-temperature fluorination treatment, effectively introducing surface fluorine functional groups without destroying the main structure of boron nitride, thereby regulating the electronic properties and surface polarity of the material and enhancing its adsorption and activation ability for persulfate.
[0026] Secondly, the applicant provides a bimetallic Fenton catalyst prepared by the above method. This catalyst is a fluorine-doped boron nitride-based bimetallic catalyst that can efficiently and environmentally activate persulfate.
[0027] Finally, the applicant provided the application of the bimetallic Fenton catalyst prepared by the above method in the degradation of antibiotic wastewater. The antibiotic wastewater contains any one of tetracycline, sulfamethoxazole, or quinolones. The above catalyst, when applied to the activation of persulfate degradation of antibiotics, exhibits excellent catalytic activity and stability.
[0028] Compared with the prior art, the present invention has the following advantages: 1) Simple preparation method and low cost: The present invention uses inexpensive and readily available boric acid, urea and fluoroborate metal salts as raw materials. The target catalyst can be obtained through simple solution mixing, oil bath evaporation and two-step pyrolysis process. No complicated equipment and harsh conditions are required, and it is easy to scale up production.
[0029] 2) Significant bimetallic synergistic effect: By introducing two different transition metals (such as Fe / Cu, Fe / Co, Cu / Co) into the precursor, a bimetallic active center is formed in the boron nitride matrix. The introduction of metal sites (such as iron, copper, cobalt, etc.) can also construct a metal-nitrogen coordination structure, forming atomically distributed metal active sites. This electron transfer and synergistic effect between the two metals significantly enhances the activation efficiency and ability of persulfate, thereby improving the degradation rate and mineralization degree of antibiotics.
[0030] 3) Secondary fluorination via re-pyrolysis for enhanced performance: The unique re-pyrolysis process is also a secondary fluorination step, introducing stable fluorine functional groups onto the boron nitride surface. The high electronegativity of fluorine can modulate the electronic structure and surface properties of the material, enhancing the interaction between the catalyst and persulfate, further improving its catalytic activity. Simultaneously, it improves the chemical stability and anti-interference ability of the material under different pH conditions, further enhancing its stability and extending the catalyst's lifespan. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application.
[0032] Figure 1 This is the XRD pattern of the catalyst in this application.
[0033] Figure 2 This is a SEM image of the catalyst in this application. Detailed Implementation
[0034] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit the technical solutions of this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without creative effort are within the scope of protection of this application.
[0035] Example 1
[0036] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.68 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and cobalt fluoroborate hexahydrate in a mass ratio of 1:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 200 W to obtain solution A. Separately weigh 7.2 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0037] (2) Mix solution A and solution B, and heat in an oil bath at 65 ℃ for 8 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 900 ℃ at 5 ℃ / min under N2 atmosphere. Hold the temperature for 2 h to obtain the primary pyrolysis product.
[0038] (3) The initial pyrolysis product obtained in step (2) is ball-milled with ammonium fluoride at a mass ratio of 1:2. The resulting mixture is placed in a tube furnace and heated to 450 °C at 3 °C / min under N2 atmosphere. The mixture is then kept at this temperature for 5 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Co / BN-1.
[0039] Characterization of the catalyst Fe-Co / BN-1: Figure 1 The XRD pattern shows diffraction peaks belonging to the (002) and (100) crystal planes of boron nitride, and no obvious metal crystallization peaks were found, indicating that the metal is distributed relatively evenly on the catalyst surface. Figure 2 The SEM images show that the catalyst exhibits a stacked sheet-like structure with a rough and porous surface.
[0040] Two mg of catalyst Fe-Co / BN-1 was added to 30 mL of a 20 mg / L tetracycline (TC) solution, followed by the addition of 1 mM persulfate (PMS). The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the degradation rate of tetracycline was 99.9%, and the PMS utilization rate was 82.5%.
[0041] Example 2
[0042] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.29 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and cobalt fluoroborate hexahydrate in a mass ratio of 4:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 200 W to obtain solution A. Separately weigh 5.2 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 15 min under the same conditions to obtain solution B.
[0043] (2) Mix solution A and solution B, and heat in an oil bath at 55 °C for 10 h with stirring at 650 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 900 °C at 5 °C / min under N2 atmosphere. Hold the temperature for 2 h to obtain the primary pyrolysis product.
[0044] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:3 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 350 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 4 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Co / BN-2.
[0045] The tests showed that the XRD and SEM spectra of catalyst Fe-Co / BN-2 were similar to those of catalyst Fe-Co / BN-1.
[0046] Two mg of catalyst Fe-Co / BN-2 was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 99.2% and the PMS utilization rate was 81.1%.
[0047] Example 3
[0048] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 0.98 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and cobalt fluoroborate hexahydrate in a mass ratio of 8:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 150 W to obtain solution A. Separately weigh 4.2 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0049] (2) Mix solution A and solution B, and heat in an oil bath at 45 °C for 12 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 900 °C at 5 °C / min under N2 atmosphere. Hold the temperature for 2 h to obtain the primary pyrolysis product.
[0050] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:1 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 400 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 4 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Co / BN-3.
[0051] The XRD and SEM spectra of catalyst Fe-Co / BN-3 are similar to those of catalyst Fe-Co / BN-1.
[0052] Two mg of catalyst Fe-Co / BN-3 was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 88.7% and the PMS utilization rate was 72.4%.
[0053] Example 4
[0054] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.12 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and cobalt fluoroborate hexahydrate in a mass ratio of 16:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 100 W to obtain solution A. Separately weigh 3.8 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0055] (2) Mix solution A and solution B, and heat in an oil bath at 65 ℃ for 8 h with stirring at 650 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 900 ℃ at 5 ℃ / min under N2 atmosphere, and keep it at the temperature for 2 h to obtain the primary pyrolysis product.
[0056] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:2 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 450 °C at 4 °C / min under a N2 atmosphere and kept at the temperature for 5 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Co / BN-4.
[0057] Two mg of the catalyst Fe-Co / BN-4 was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 84.4% and the PMS utilization rate was 68.9%.
[0058] Example 5
[0059] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.52 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and cobalt fluoroborate hexahydrate in a mass ratio of 3:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 150 W to obtain solution A. Separately weigh 6.8 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0060] (2) Mix solution A and solution B, and heat in an oil bath at 60 °C for 9 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 800 °C at 5 °C / min under N2 atmosphere. Hold the temperature for 3 h to obtain the primary pyrolysis product.
[0061] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:2 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 350 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 4 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Co / BN-5.
[0062] Two mg of the catalyst Fe-Co / BN-5 was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 86.5% and the PMS utilization rate was 70.6%.
[0063] Example 6
[0064] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 0.72 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and copper fluoroborate hexahydrate in a mass ratio of 4:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 150 W to obtain solution A. Separately weigh 3.5 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0065] (2) Mix solution A and solution B, and heat in an oil bath at 55 °C for 10 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 800 °C at 5 °C / min under N2 atmosphere. Hold the temperature for 2 h to obtain the primary pyrolysis product.
[0066] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:1 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 350 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 5 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Cu / BN-1.
[0067] Two mg of catalyst Fe-Cu / BN-1 was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 95.8% and the PMS utilization rate was 78.1%.
[0068] Example 7
[0069] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.48 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and copper fluoroborate hexahydrate in a mass ratio of 1:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 200 W to obtain solution A. Separately weigh 7.2 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0070] (2) Mix solution A and solution B, and heat in an oil bath at 65 ℃ for 8 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 900 ℃ at 5 ℃ / min under N2 atmosphere. Hold the temperature for 2 h to obtain the primary pyrolysis product.
[0071] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:2 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 450 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 5 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Cu / BN-2.
[0072] Two mg of catalyst Fe-Cu / BN-2 was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 94.1% and the PMS utilization rate was 81.1%.
[0073] Example 8
[0074] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.96 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and indium fluoroborate hexahydrate in a mass ratio of 4:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 200 W to obtain solution A. Separately weigh 7.2 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0075] (2) Mix solution A and solution B, and heat in an oil bath at 65 ℃ for 8 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 1000 ℃ at 5 ℃ / min under N2 atmosphere, and keep it at the temperature for 2 h to obtain the primary pyrolysis product.
[0076] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:3 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 550 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 3 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-In / BN.
[0077] Two mg of the catalyst Fe-In / BN was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 89.2% and the PMS utilization rate was 74.6%.
[0078] Example 9
[0079] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 1.17 g of fluoroborate metal salt (ferrous fluoroborate hexahydrate and lead fluoroborate hexahydrate in a mass ratio of 8:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 30 kHz and input power of 100 W to obtain solution A. Separately weigh 4.5 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0080] (2) Mix solution A and solution B, and heat in an oil bath at 65 ℃ for 8 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 900 ℃ at 5 ℃ / min under N2 atmosphere. Hold the temperature for 2 h to obtain the primary pyrolysis product.
[0081] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:2 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 550 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 2 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Fe-Pb / BN.
[0082] Two mg of the catalyst Fe-Pb / BN was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 83.8% and the PMS utilization rate was 68.4%.
[0083] Example 10
[0084] This embodiment provides a bimetallic Fenton catalyst, the preparation method of which is as follows: (1) Weigh 1.23 g of boric acid and 0.92 g of fluoroborate metal salt (copper fluoroborate hexahydrate and cobalt fluoroborate hexahydrate in a mass ratio of 5:1), dissolve them together in 50 mL of deionized water, and sonicate for 30 min under ultrasonic frequency of 40 kHz and input power of 200 W to obtain solution A. Separately weigh 4.3 g of urea and dissolve it in 50 mL of deionized water, and sonicate for 30 min under the same conditions to obtain solution B.
[0085] (2) Mix solution A and solution B, and heat in an oil bath at 65 ℃ for 8 h with stirring at 850 rpm to evaporate the water and obtain the precursor. Grind the precursor into powder, place it in a tube furnace, and heat it to 800 ℃ at 5 ℃ / min under N2 atmosphere. Hold the temperature for 3 h to obtain the primary pyrolysis product.
[0086] (3) The initial pyrolysis product obtained in step (2) is mixed with ammonium fluoride at a mass ratio of 1:1 and ground evenly with an agate mortar. The mixture is placed in a tube furnace and heated to 350 °C at 3 °C / min under a N2 atmosphere and kept at the temperature for 5 h to obtain a fluorine-doped boron nitride-based bimetallic catalyst, denoted as catalyst Cu-Co / BN.
[0087] Two mg of the catalyst Cu-Co / BN was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 80.6% and the PMS utilization rate was 65.8%.
[0088] Comparative Example 1
[0089] The setup for this comparative example is the same as that for Example 1, except that the metal salt of fluoroborate is ferrous fluoroborate hexahydrate, and the final product is a fluorine-doped boron nitride-based monometallic catalytic material, denoted as catalyst Fe / BN.
[0090] Two mg of the catalyst Fe / BN was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 68.6% and the PMS utilization rate was 56.0%.
[0091] Comparative Example 2
[0092] The setup for this comparative example is the same as that for Example 1, except that the metal salt of fluoroborate is copper fluoroborate hexahydrate, and the final product is a fluorine-doped boron nitride-based monometallic catalytic material, denoted as catalyst Cu / BN.
[0093] Two mg of the catalyst Cu / BN was added to 30 mL of a 20 mg / L tetracycline solution, along with 0.1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High performance liquid chromatography and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 72.3% and the PMS utilization rate was 59.0%.
[0094] Under the same conditions, compared with the degradation rate of 99.9% and PMS utilization of 82.5% in Example 1, the degradation effects of the single-metal catalysts Fe / BN and Cu / BN on antibiotic wastewater were significantly lower than those in Example 1. Combining the above examples, it can be seen that this application, by introducing two different transition metals (such as Fe / Cu, Fe / Co, Cu / Co) into the precursor, forms a bimetallic active center in the boron nitride matrix, enabling electron transfer and synergistic effects between the two metals, significantly enhancing the activation efficiency for persulfate, thereby improving the degradation rate and mineralization degree of antibiotics.
[0095] Comparative Example 3
[0096] The setup for this comparative example is the same as that for Example 1, except that the fluorine modification in step three was not performed, and the preliminary pyrolysis product was used directly as the catalyst material, denoted as catalyst Fe-Co / BN-no.
[0097] Two mg of the catalyst Fe-Co / BN-no was added to 30 mL of a 20 mg / L tetracycline solution, along with 1 mM peroxymonosulfate. The mixture was stirred at room temperature for 20 min. High-performance liquid chromatography (HPLC) and UV-Vis spectrophotometry showed that the tetracycline degradation rate was 85.2% and the PMS utilization rate was 66.3%.
[0098] In the above embodiment, a fluorinating agent was introduced in step three, and a secondary fluorination process occurred during the re-pyrolysis. This process introduced stable fluorine functional groups onto the surface of boron nitride. The high electronegativity of fluorine can regulate the electronic structure of the material surface and enhance the interaction between the catalyst and persulfate. Therefore, under the same conditions, the tetracycline degradation rate of Example 1 was as high as 99.9%, and the PMS utilization rate was as high as 82.5%, while the tetracycline degradation rate of Comparative Example 3 was only 85.2%, and the PMS utilization rate was only 66.3%.
[0099] The above case studies significantly enhanced the activation efficiency of persulfate through bimetallic synergistic effects and secondary fluorination surface modification, overcoming the shortcomings of traditional zero-valent iron catalysts such as easy leaching of metal ions and low catalytic activity. It also demonstrated excellent degradation performance on antibiotic wastewater, providing a new approach for the green and efficient treatment of antibiotic-containing wastewater and showing great potential for practical application.
[0100] The above-described embodiments are merely illustrative of several feasible implementations of the present invention, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of the present invention, nor are the embodiments intended to limit the scope of protection in the claims of the present invention. For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention. All equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A method for preparing a bimetallic Fenton catalyst, characterized in that, The steps are as follows: Step 1: Fluoroborate metal salt and boric acid are dispersed in deionized water to obtain solution A, wherein the fluoroborate metal salt contains at least two metal salts; urea is dissolved in deionized water to obtain solution B; Step 2: Mix solution A and solution B, evaporate to dryness in an oil bath to obtain a precursor. Place the precursor in a tube furnace and perform initial pyrolysis under a nitrogen atmosphere. Urea, as the nitrogen source, reacts with boric acid to generate boron nitride. At the same time, the fluoroborate metal salt decomposes, allowing metal atoms to be doped into the boron nitride lattice or loaded onto its surface. Step 3: Add fluorinating agent to the pyrolysis product, mix evenly using a ball mill, and then place it in a tube furnace for re-pyrolysis under a nitrogen atmosphere to obtain a bimetallic Fenton catalyst.
2. The method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: In step one, the fluoroborate metal salt is any two of ferrous fluoroborate hexahydrate, copper fluoroborate hexahydrate, cobalt fluoroborate hexahydrate, lead fluoroborate, and indium fluoroborate.
3. The method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: The molar ratio of urea to boric acid is 1:1 to 16:1, and the ratio of the total mass of urea and boric acid to the mass of fluoroborate metal salt is 4:1 to 7:
1.
4. The method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: The oil bath temperature for drying in the oil bath is 45–65 °C.
5. The method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: The initial pyrolysis temperature is 800–1000 °C, and the duration is 1–3 h.
6. The method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: The fluorinating agent is at least one of ammonium fluoride, ammonium hydrogen fluoride, sodium fluoride, and calcium fluoride.
7. The method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: The mass ratio of the fluorinating agent to the pyrolysis product is 1:1 to 1:
3.
8. The method for preparing a fluorine-doped boron nitride-based bimetallic Fenton catalyst according to claim 1, characterized in that, The ball milling time is 2 to 4 hours, and the ball milling speed is 300 to 500 rpm.
9. A method for preparing a bimetallic Fenton catalyst according to claim 1, characterized in that: The re-pyrolysis temperature is 350–550 °C, and the duration is 1–3 h.
10. The application of a bimetallic Fenton catalyst prepared by the method according to any one of claims 1 to 9 in the degradation of antibiotic wastewater.
